2023
DOI: 10.3389/fendo.2023.1096950
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin level is associated with fall risk, muscle strength, and cortical porosity in postmenopausal women

Abstract: BackgroundIrisin plays a role in bone-muscle crosstalk, but the relationship between the serum irisin level and bone microarchitecture remains unknown.ObjectiveThis study aimed to investigate the relationships between serum irisin level and fall risk, muscle strength, bone mineral density (BMD), and bone microarchitecture among Chinese postmenopausal women.MethodsIn all 138 postmenopausal women, handgrip strength, short physical performance battery (SPPB), and the timed up-and-go test were performed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, muscle metabolism is primarily regulated by Irisin, a pro-myogenic factor derived from the fibronectin type III domain-containing protein 5 (FNDC5), attributed to skeletal muscle hypertrophy and increased protein synthesis via the AKT/mTOR pathway [8]. Several studies have reported an association between low circulating Irisin levels and low muscle and bone mass; however, its relationship with fat and lean body mass remains uncertain [10,11]. These various signaling pathways ultimately exert autocrine, paracrine, and endocrine effects on bone and muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, muscle metabolism is primarily regulated by Irisin, a pro-myogenic factor derived from the fibronectin type III domain-containing protein 5 (FNDC5), attributed to skeletal muscle hypertrophy and increased protein synthesis via the AKT/mTOR pathway [8]. Several studies have reported an association between low circulating Irisin levels and low muscle and bone mass; however, its relationship with fat and lean body mass remains uncertain [10,11]. These various signaling pathways ultimately exert autocrine, paracrine, and endocrine effects on bone and muscle.…”
Section: Introductionmentioning
confidence: 99%